How Jordanian Students Learn about Americans? A Case Study at Yarmouk University in Irbid, Jordan - Irene Gibson; Mohammed S. Banihani (Sultan Qaboos University, 2017)
This study investigated how educational programs affect Jordanian students‟ perceptions of Americans. Students were from Yarmouk University in Jordan. The focus was twofold: first, to document opinions about Americans and American-related topics. Second, to determine if various educational programs relating to Americans impact opinions about Americans. The focus of the study compared students involved in cultural exchange programs to students not involved in exchange programs. This study was based on a questionnaire distributed to a purposeful sample of undergraduate and graduate students at Yarmouk University. Participation in a cultural exchange program was found to not have a significant effect on opinion of Americans. Program participants reported a greater proportion of "very positive" opinions of Americans, and did not hold "very negative" opinions of Americans, but these differences were not statistically significant. When comparing average opinions on Americans and related questions, exchange participants reported on average more positive opinions in cultural categories, but more negative opinions in governmental categories. The average confidence in knowledge about Americans was higher in exchange participants than the confidence of non-participants. Having a more positive opinion of the U.S., American ideas about democracy, American music, movies, and television, and desire to travel to the U.S. all were significantly associated with a more positive opinion about Americans.